Comparative Efficacy of Commercial Liquid and Mat-Type Electric Vaporizer Insecticides Against Asian Tiger Mosquito (Diptera: Culicidae). Issue 6 (22nd May 2021) - Jung, Hun; An, Huijun; Lee, Minjin; Lee, Jieun; Tak, Jun-Hyung
Abstract: Mat and liquid-type electric insecticide vaporizers continuously emit insecticides into the surrounding air. Because both the target insects, mostly mosquitoes, and humans are exposed to those insecticides, it is crucial to understand and monitor their deposition and spatial distribution in treated areas. In the current study, we examined the evaporation of insecticides from seven commercial liquid and mat vaporizers and measured their knock-down and insecticidal activity against the adult females of the Asian tiger mosquito, Aedes albopictus (Skuse). Electric vaporizers from three manufactures had differences in their heaters and active ingredients. Most had continued evaporation during hourly and daily monitoring; however, some liquid vaporizers failed to continue emission to their designated end periods. Overall, mosquitoes located at the upper position in a Peet-Grady chamber and in a field-simulation room exhibited faster knock-down activity than did mosquitoes in other areas, indicating that the insecticides accumulated on the ceiling area. Although most of mat and liquid vaporizers had <60 min of average KT90 values when tested in the Peet-Grady chamber (1.8 × 1.8 × 1.8 m), they failed to have any knock-down in 2 h of observation in the field-simulation room (6.8 × 3.4 × 2.7 m) but showed 72. 8 ± 11.7% and 56. 7 ± 7.3% knock-down in the mat and liquid vaporizers, respectively, in 3 h of operation. Further study will be required to examine whether this relatively limited efficacy can be compensated by other physiological and behavioral effects, including disruption in host-seeking or blood-sucking activities.